Flexible Pavement Distress Analysis Using the Pavement Condition Index (PCI) Method - Rajak, Irsandi A; Altarans , Indra; Faruk, Fitriyanti (SCIENTIA: Journal of Multi Disciplinary Science, 2025)
Road infrastructure along the Kalaodi–Fabaharu corridor in Tidore Kepulauan has exhibited varying levels of surface deterioration, highlighting the need for an objective and standardized evaluation to determine appropriate treatment priorities. This study aims to assess the condition of flexible pavement using the Pavement Condition Index (PCI) method while also identifying key factors contributing to the observed damage. Field surveys were conducted on twenty selected road segments to record distress types, severity levels, and the extent of deterioration in accordance with ASTM D6433-11 guidelines. These data were then used to calculate PCI values, enabling the classification of pavement conditions across the study area. The findings show that PCI values range from 15 to 56, with an overall average of 27.48, indicating that the general pavement condition falls within the "Poor" category. The most prevalent distress types identified include alligator cracking, potholes, and raveling, which are primarily associated with inadequate drainage systems, environmental influences such as rainfall and surface runoff, and the lack of routine maintenance, rather than significant traffic loading. These contributing factors collectively accelerate pavement degradation and reduce structural performance over time. Based on the assessment results, the study concludes that the analyzed road corridor requires a phased and prioritized repair strategy. Immediate interventions should focus on patching critical failures and improving drainage performance to prevent further deterioration. Subsequent actions should include periodic rehabilitation for moderately damaged segments and full reconstruction for road sections exhibiting severe structural distress. This systematic approach is essential to restoring pavement functionality and ensuring long-term serviceability of the Kalaodi–Fabaharu road network.